2011
DOI: 10.1007/s00421-011-2230-7
|View full text |Cite
|
Sign up to set email alerts
|

Validity, reliability and stability of the portable Cortex Metamax 3B gas analysis system

Abstract: This study investigated the performance of the portable Cortex Metamax 3B (MM3B) automated gas analysis system during both simulated and human exercise using adolescents. Repeated measures using a Gas Exchange System Validator (GESV) across a range of simulated metabolic rates, showed the MM3B to be adequately reliable (both percentage errors, and percentage technical error of measurements <2%) for measuring expired ventilation (VE), oxygen consumption (VO2), and carbon dioxide production (VCO2). Over a 3 h pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(94 citation statements)
references
References 20 publications
5
87
0
2
Order By: Relevance
“…The measurement accuracy of the system in the present study was shown to be much better than that of some portable systems. Macfalane and Wong 15) reported that for the Metamax 3B (Cortex, Leipzig, Germany), the V ・ O2…”
Section: Discussionmentioning
confidence: 99%
“…The measurement accuracy of the system in the present study was shown to be much better than that of some portable systems. Macfalane and Wong 15) reported that for the Metamax 3B (Cortex, Leipzig, Germany), the V ・ O2…”
Section: Discussionmentioning
confidence: 99%
“…In the professional performance diagnostics, it is used to determine oxygen consumption, CO 2 emission and the respiratory minute volume, particularly for accurate determination of energy expenditure (in accordance with standard specifications, DIN EN ISO 8996: 2004). The technical failure of this unit is less than 2% [13]. The handy and user-friendly psychophysiological ambulatory Movisens measurement system optimizes research applications and records, a single channel ECG via dry electrodes built in a chest strap without disturbing the subject [14].…”
Section: Methodsmentioning
confidence: 99%
“…Resting metabolic rate (RMR) was measured by indirect calorimetry using measurement of VO 2 and VCO 2 (MetaMax 3B, Cortex, Biophysik, Germany) [ 28 ] . The MetaMax 3B system analyzer unit was calibrated according to the manufacturer's instructions before each testing session.…”
Section: Resting Metabolic Ratementioning
confidence: 99%